Improving through employee participation: The case of a Spanish food manufacturer - Iván González-Boubeta; Iago Portela-Caramés; J. Carlos Prado-Prado (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: Employee participation is considered a fundamental pillar to implement continuous improvement. Based on this consideration, this article presents an action research case study in a large food manufacturer where employee participation is implemented. The experience has a two-fold objective: improve performance of the production system and make the participative philosophy deep-rooted among workers. Design/methodology/approach: The authors implement a structured participation system, establishing an approach of empowerment and focusing on the creation of suitable organizational structures. Under those premises, improvement teams were created on each of the firm's production lines. Once the participation of the workers is finished, they were given a questionnaire to assess how deep-rooted the participative culture had become. Findings: The results show a remarkable improvement in the efficiency of manufacturing processes, as well as the consolidation of a participative philosophy. However, there are notable differences in the results obtained for each improvement team. Research limitations/implications: The differences obtained in the results highlight certain issues that future research must tackle. These include the way in which the staff should be rewarded for their participation or what the influence of the organizational context is when setting improvement objectives. Practical implications: The positive results obtained support the methodology proposed by the authors for structuring participation. Organizations can set up projects of this type to improve their competitiveness while at the same time strengthening the commitment of their personnel. Originality/value: This is one of the first studies in the field of employee participation that jointly assess the economic area and the cultural and organizational plane.
Keywords: 650; Employee participation; employee empowerment; improvement teams; efficiency; lean management; action research